Statistical and fuzzy approaches to data processing, with applications to econometrics and other areas : in honor of Hung T. Nguyen's 75th birthday /: in honor of Hung T. Nguyen's 75th birthday. ([2021]) - Kreinovich, Vladik
No abstract available